Public Perception of Religious Moderation on Twitter: The Case of Kicking Offerings on Mount Semeru, Lumajang - Farlina, Nina; Sulaiman, Setyadi; Bagaskara, Faishal Sultan (SHAHIH: Journal of Islamicate Multidisciplinary, 2024)
This study aims to analyze the construction of public opinion and perception regarding religious moderation in the context of Mount Semeru incident, Lumajang, Indonesia, (2022). This research employs a qualitative approach, utilizing perception theory and virtual ethnographic analysis to examine Twitter users' responses to a viral video depicting individuals disrupting traditional offerings at Mount Semeru, also investigates how Twitter as a social media platform influences public perception of religious moderation. The findings reveal three distinct response categories: opposition, support, and moderation, which contributed to digital conflicts. To minimize digital conflicts, especially intolerant responses on social media, there is a need to strengthen religious moderation on social media through education content grounded in Islamic scriptures (Quran and Hadith), Indonesian state ideology (Pancasila), and collaboration with religious authorities via digital media formats. The research demonstrates the significant role of social media in shaping public perceptions of religious tolerance in contemporary Indonesia.